Echoes of the Day: Exploring the Interplay Between Daily Contexts and Smartphone Push Notification Experiences - Mustafa Can Özdemir; Mati Mottus; David Lamas (Applied Sciences)
Smartphone push notifications aim to provide time-sensitive information to their users. However, notifications are often transmitted in ill-timed situations, causing users to be interrupted, annoyed, and stressed. This ultimately affects the overall notification experience as it does not consider the external contexts the users are situated in. This study aims to shed light on how users manage notifications in their daily lives and how they perceive the experience as a whole. A total of 28 participants took part in a 5-day mixed-method diary study, which logged a total of 135 entries. Based on this, six types of characteristics emerged. These characteristics were formed from the combination of three main categories: notification related, day related, and user related. The findings of this study highlight implementing different strategies for each type of characteristic to mitigate the adverse effects notifications have on users.